2011
DOI: 10.1016/j.ijpara.2011.10.001
|View full text |Cite
|
Sign up to set email alerts
|

The Trichomonas vaginalis hydrogenosome proteome is highly reduced relative to mitochondria, yet complex compared with mitosomes

Abstract: The human pathogen Trichomonas vaginalis lacks conventional mitochondria and instead contains divergent mitochondrial-related organelles. These double-membrane bound organelles, called hydrogenosomes, produce molecular hydrogen. Phylogenetic and biochemical analyses of hydrogenosomes indicate a common origin with mitochondria; however identification of hydrogenosomal proteins and studies on its metabolism have been limited. Here we provide a detailed proteomic analysis of the T. vaginalis hydrogenosome. The pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
120
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(125 citation statements)
references
References 114 publications
(211 reference statements)
3
120
0
2
Order By: Relevance
“…Through the HA-tagged TvATP-PFK1, products of four paralogous TvATP-PFK genes were immunoprecipitated from isolated hydrogenosomes and identified by mass spectrometry. Earlier proteomic studies suggested association of the glycolytic pathway, including TvATP-PFK, with the hydrogenosome (13,15), which raises the question of whether glycolytic enzymes form functional protein complexes on the hydrogenosomal outer membrane, as has been shown for mitochondria. For example, in Arabidopsis thaliana, 5 to 10% of each glycolytic enzyme is associated with the outer mitochondrial surface.…”
Section: Figmentioning
confidence: 96%
See 1 more Smart Citation
“…Through the HA-tagged TvATP-PFK1, products of four paralogous TvATP-PFK genes were immunoprecipitated from isolated hydrogenosomes and identified by mass spectrometry. Earlier proteomic studies suggested association of the glycolytic pathway, including TvATP-PFK, with the hydrogenosome (13,15), which raises the question of whether glycolytic enzymes form functional protein complexes on the hydrogenosomal outer membrane, as has been shown for mitochondria. For example, in Arabidopsis thaliana, 5 to 10% of each glycolytic enzyme is associated with the outer mitochondrial surface.…”
Section: Figmentioning
confidence: 96%
“…Therefore, it was surprising that genes for ATP-dependent phosphofructokinase (ATP-PFK) turned up in the Trichomonas genome (12). Furthermore, peptides of the expressed protein were found in the hydrogenosomal proteome (13-15), although the exact topology of hydrogenosome-associated T. vaginalis ATP-PFK (TvATP-PFK) remains unclear (13,15). PP i -PFK and ATP-PFK share an evolutionary origin (16,17).…”
mentioning
confidence: 99%
“…For example, members of the Neocallimastigomycota have adapted a strict anaerobic lifestyle. Similar to other anaerobic eukaryotes (e.g., Trichomonas vaginalis [6,7]), their mitochondria have undergone a reductive evolution process to a hydrogenosome, an organelle whose main function is ATP production via substrate-level phosphorylation and hydrogen production (6,8,9). Anaerobic fungi also reproduce asexually via the release of motile flagellated zoospores from zoosporangia that develop during rhizoidal fungal growth (10,11).…”
mentioning
confidence: 99%
“…The cell also possesses an axostyl, a bundle of microtubules passing through the cell along its anterior-posterior axis into the extracellular environment , which has a function in cell attachment and mitosis (Ribeiro et al, 2000). The cytoplasm contains a single defined nucleus, and several hydrogenosomes; primitive redox organelles, evolved from mitochondria, which produce molecular hydrogen and ATP (Schneider et al, 2011).…”
Section: Morphologymentioning
confidence: 99%